Intestinal Parasites Coinfection Does Not Alter Plasma Cytokines Profile Elicited in Acute Malaria in Subjects from Endemic Area of Brazil - Juan Camilo Sánchez-Arcila; Daiana de Souza Perce-da-Silva; Mariana Pinheiro Alves Vasconcelos; Rodrigo Nunes Rodrigues-da-Silva; Virginia Araujo Pereira; Cesarino Junior Lima Aprígio; Cleoni Alves Mendes Lima; Bruna de Paula Fonseca e Fonseca; Dalma Maria Banic; Josué da Costa Lima-Junior; Joseli Oliveira-Ferreira (Mediators of Inflammation)
In Brazil, malaria is prevalent in the Amazon region and these regions coincide with high prevalence of intestinal parasites but few studies explore the interaction between malaria and other parasites. Therefore, the present study evaluates changes in cytokine, chemokine, C-reactive protein, and nitric oxide (NO) concentrations in 264 individuals, comparing plasma from infected individuals with concurrent malaria and intestinal parasites to individuals with either malaria infection alone and uninfected. In the studied population 24% of the individuals were infected with Plasmodium and 18% coinfected with intestinal parasites. Protozoan parasites comprised the bulk of the intestinal parasites infections and subjects infected with intestinal parasites were more likely to have malaria. The use of principal component analysis and cluster analysis associated increased levels of IL-6, TNF-α, IL-10, and CRP and low levels of IL-17A predominantly with individuals with malaria alone and coinfected individuals. In contrast, low levels of almost all inflammatory mediators were associated predominantly with individuals uninfected while increased levels of IL-17A were associated predominantly with individuals with intestinal parasites only. In conclusion, our data suggest that, in our population, the infection with intestinal parasites (mainly protozoan) does not modify the pattern of cytokine production in individuals infected with P. falciparum and P. vivax.